Domestic Electrical Load Management Using Smart Grid. (November 2016) - Rauf, S.; Rasool, S.; Rizwan, M.; Yousaf, M.; Khan, N.
Abstract: Demand side load management is one of the basic features in smart grid, which enable end users to know major characteristics about their energy consumption during peak and off peak hours and encourage the utility to maintain load demand in extreme conditions. This results in more reliable system with overall improvement of efficiency and low CO2 emission in smart grid. Most of the previous techniques used in demand side load management are specific to traditional energy management strategies with limited number of load controlling technologies. In this paper, we focus on operating the system with more efficiency and reliability. Integration of solar PV distributed generation, smart DC storage and smart load is expected to add valuable operations in the smart grid. Direct load control (DLC) and load shifting techniques for overkill load offers various outcomes during extreme conditions.